Determination of the internal pair production branching ratio of 90Y. (February 2020) - Pibida, L.; Zimmerman, B.E.; King, L.; Fitzgerald, R.; Bergeron, D.E.; Napoli, E.; Cessna, J.T.
Abstract: The National Institute of Standards and Technology (NIST) measured the internal pair production branching ratio of 90 Y using two sources and four high purity germanium (HPGe) detectors to detect the resulting annihilation radiation. The internal pair production branching ratio determined from these measurements, (32.0 ± 1.5) × 10 −6 ( k = 1), agrees within 1 standard uncertainty with the recommended value of (32.6 ± 0.7) × 10 −6 ( k = 1) from the DDEP database. Highlights: Measured internal pair production branching ratio of Y-90. Used high-purity germanium detectors for gamma-ray spectrometry. Result in good agreement with literature.